DAMPAK WISATA RELIGI MAKAM SUNAN GUNUNG DJATI DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Syaeful Bakhri; Shifa Nurul Hilma; Sya’adatun Munawaroh; Mauliandini Mufidah; Indah Nurhaeni; Nudza Ainandeka De Fatih; Ardiansyah Ardiansyah (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2021)
This study tries to conduct research on religious tourism, especially pilgrimage tourism, which is a type of tourism and activity that is often carried out by the people of Indonesia. The activities of religious tourism visitors also have an impact on the welfare of the surrounding community, meaning that there is a symbiotic mutualism between visitors and the surrounding community. The method used in this study is a descriptive quantitative approach, with variable measurements symbolized by numbers and then analyzed with statistical tools to draw conclusions on each variable. The population in this study is the residents of Gunung Djati District where the community gets a direct impact from the existence of the Sunan Gunung Djati tomb. Sampling was carried out using purposive sampling with the condition that the respondents were residents of the Gunung Djati sub-district and had direct activities with the existence of the Gunung Djati tomb tourism, totaling 100 respondents. The results of the analysis and data processing state that the variable (X) of religious tourism has a positive and significant influence on improving people's welfare (Y) with a value of r, then R Square of 0.476 indicates the level of influence of religious tourism on increasing community welfare with a percentage of influence of 47.6%. This means that the existence of religious tourism is able to improve the welfare of the community, especially in increasing daily income and being able to open up employment opportunities.